1947
DOI: 10.1017/s0080456800004774
|View full text |Cite
|
Sign up to set email alerts
|

XII.—The Blind Seed Disease of Rye-Grass and its Causal Fungus

Abstract: The presence of a fungus on grains of perennial rye-grass which failed to germinate was recorded in New Zealand by Hyde in 1932. In 1938 the same fungus was associated by Hyde with exceptionally low germination in Italian rye-grass and, later that year (Hyde, 1938 a), the poor germinating capacity was ascribed to infection by Pullularia. Seed of the Scottish harvest of 1938 showed the signs of infection by Pullularia described in Hyde's papers (Noble, 1939), and cultures obtained from mycelium within infected … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
23
0

Year Published

1950
1950
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(25 citation statements)
references
References 11 publications
2
23
0
Order By: Relevance
“…Wilson, Noble and Gray, was described by Neill & Hyde (1939) who surveyed the incidence of the disease in New Zealand perennial ryegrass seed samples and described the etiology of the pathogen, after earlier work by Hyde (1932) had established the presence of fungal mycelium and spores in ryegrass seed of low germination. These findings were confirmed by Calvert & Muskett (1945) and Wilson et al (1945). Since then, the disease has been reported from most ryegrass seed-producing countries and has been recognised as being of economic importance in Oregon, New Zealand, and Britain (Wright 1967).…”
Section: Introductionsupporting
confidence: 62%
“…Wilson, Noble and Gray, was described by Neill & Hyde (1939) who surveyed the incidence of the disease in New Zealand perennial ryegrass seed samples and described the etiology of the pathogen, after earlier work by Hyde (1932) had established the presence of fungal mycelium and spores in ryegrass seed of low germination. These findings were confirmed by Calvert & Muskett (1945) and Wilson et al (1945). Since then, the disease has been reported from most ryegrass seed-producing countries and has been recognised as being of economic importance in Oregon, New Zealand, and Britain (Wright 1967).…”
Section: Introductionsupporting
confidence: 62%
“…These results confirm the previously published work of CALVERT and MUSKETT (1), GEMMELL (3), NEILL and HYDE (9), and WILSON, NOBLE and GRAY (11), who all suggest that the commercial strains tend to be less susceptible to attack by G. temulenta than the pedigree ones. The results also confirm the suggestions of CALVERT and MUSKETT (2), NOBLE and GRAY (10), GORMAN (4, 5), and LITHGOW and COTTIER (8), that a vigorously growing crop is less susceptible to attack than a thin, poor one.…”
Section: Discussionsupporting
confidence: 92%
“…From this, it would appear that, unless the heads were covered (as reported in only one case by GORMAN (5)) the chances of preventing infection by smothering are very small, as it can take place at any time from anthesis up to one week before harvesting, according to LITHGOW and COTTIER (8). WILSON, NOBLE and GRAY (11) suggest that the reduction in the degree of infection may be due to a change in the plant, such as increased vigour, and the results of this trial seem to support this. A method of control needs to be developed which will give a reduction in the incidence of the disease, particularly with the valuable pedigree strains.…”
Section: Discussionmentioning
confidence: 52%
See 1 more Smart Citation
“…Hampton & Scott (1980) reviewed the literature and suggested that the explanations previously suggested for the link between a reduction in blind seed disease and high fertility were not satisfactory, and that two other possibilities, originally suggested by Wilson et at. (1945), should be investigated: viz, that the use ofnitrogenous fertilisers altered the soil reaction and hence had some effect on apothecial development; that a vigorously growing crop may be physiologically less susceptible to attack than a poor thin one.…”
Section: Introductionmentioning
confidence: 99%